DESCRIPTION OF COOPERATION CULTURE ACTUALIZATION TEACHERS AND PARENTS IN MOTIVATION CHILDREN LEARN AT SDN 41 HULONTHALANGI, GORONTALO CITY - Salma Halidu; Wahyuni S. Manang (International Journal of Innovations in Engineering Research and Technology, 2021)
This descriptive study with qualitative approach aimed to determine the actualization of teamwork culture between teachers and parents at SD 41 Hulonthalangi State Elementary School in Gorontalo City. This was based on the research problem. The subjects were the principal, teachers, and parents. Further, the data were collected through direct observation, interviews, and documentation. The results showed that the actualization of teamwork culture ran well as seen from the following findings: (1) The involvement of parents in teachers and student’s activities according to the necessities and expertise of each parent. (2). The establishment of good communication between teachers and parents. (3). The efforts that were made by the school in optimizing cooperation by providing the best services.